The Causal of Stem Rot of Banana Grown in Jaffna Peninsula - Thiruchchelvan, N.; Thirukkumaran, G.; Mikunthan, G. (Academic Journal of Plant Sciences, 2012)
Stem rot of banana caused by Basidiomycetes fungus, Marasmiellus sp. (Agaricales: Tricholomataceae) is new and confined to Valikamam division of Jaffna peninsula, Sri Lanka. Symptoms of stem rot were rotted patches on rhizome and pseudo stem, gradual wilting of leaves from lower area to upper part of plant canopy, stunted growth, abnormal leaves and bunches, toppling of crown and fruiting body adhere on pseudo stem. A banana field at Thirunelvely, recorded disease incidence as high as 44.44%. The disease severity was 96.3% in left out portion of pseudostem, which yielded bunch already, 62.63% in mature plants and 23.02% in suckers. An antagonistic fungus, Trichoderma spp. showed suppressive effect on Marasmiellus sp. grown on PDA by using dual culture technique. Trichoderma harzianum and T. viride inhibited 80.6% and 92% mycelia growth of Marasmiellus sp, respectively. Poison food method revealed that maximum inhibition was with Azadirachta indica (79.19%) and Ocimum sanctum (59.96%) than Lantana camara, Zingeber officinale and Curcuma longa under in-vitro conditions. This information will help to create awareness among extension workers and growers about Marasmiellus sp. causing stem rot disease on banana in Jaffna peninsula and also helpful to restrict its spread in newer areas through infected suckers and other means
Keywords: Banana; Bio control; Marasmiellus sp; Plant extract; Stem rot; Trichoderma spp